Antara child protection dan child liberation (Dilema Kebijakan Perlindungan Hak-hak Anak di Indonesia) - Afandi, Muhrisun (Musawa Jurnal Studi Gender dan Islam, 2006)
Determining children's rights and self detemtination has been problematic in the discussion of child welfare in Indonesia. Indonesian law regards children's rights as defined solely by the basis of age, regardless of a child's competence. This could be seen from the government policies that mention that children's rights are formulated as protection rights, which has been criticized as being a denial of the autonomy and capacity of the child, in the sense that they are considered incompetent and need to be taken care and protected by adults. However, in some cases the behavior of children from some populations demonstrates that they are more mature than the general population in their age range, so that their rights should not be based solely on the basis of their age without considering their competence and autonomy. Efforts to provide more and better defined legislation on child welfare in Indonesia have been an ongoing struggle for activists and various parties. The child liberationist formulations of children's rights seems to offer the greatest possibility for a child's autonomy in relation to children's rights, which is also a critique of the tendency to underestimate the capacities of children and the general belief in the lack child's competency in society.